EBV+ high‐grade B cell lymphoma with MYC and BCL2 and/or BCL6 rearrangements: a multi‐institutional study. Issue 3 (16th December 2021) - Liu, Hui; Xu‐Monette, Zijun Y; Tang, Guilin; Wang, Wei; Kim, Young; Yuan, Ji; Li, Yu; Chen, Weina; Li, Yanping; Fedoriw, George Y; Zhu, Feng; Fang, Xiaosheng; et al.
Abstract : Aims: It is unknown whether Epstein–Barr virus (EBV) infection can occur in high‐grade B cell lymphoma with MYC and BCL2 and/or BCL6 rearrangements, also known as double‐ or triple‐hit lymphoma (DHL/THL). Methods and results: Here we report 16 cases of EBV + DHL/THL from screening 846 cases of DHL/THL and obtaining additional EBV + cases through multi‐institutional collaboration: eight MYC and BCL2 DHL, six MYC and BCL6 DHL and two THL. There were eight men and eight women, with a median age of 65 years (range = 32–86). Two patients had a history of follicular lymphoma and one had AIDS. Nine of 14 patients had an International Prognostic Index of ≥3. Half of the cases showed high‐grade/Burkitt‐like morphology and the other half diffuse large B cell lymphoma morphology. Using immunohistochemistry, the lymphoma cells were positive for MYC ( n  = 14 of 16), BCL2 ( n  = 12 of 16), BCL6 ( n  = 14 of 16), CD10 ( n  = 13 of 16) and MUM1 ( n  = six of 14). Using Hans' algorithm, 13 cases were classified as germinal centre B cell (GCB) and three as non‐GCB. The lymphomas frequently showed an EBV latency Type I with a median EBV‐encoded small RNAs of 80% positive cells (range = 20–100%). After a median follow‐up of 36.3 months (range = 2.0–41.6), seven patients died, with a median survival of 15.4 months (range = 3.4–47.3) after diagnosis of EBV + DHL/THL. Five of six patients with MYC and BCL6 DHL were alive, including four in complete remission. In contrast, only four of 10 patients with MYC and BCL2 DHL or THL were alive, including two in complete remission. The median survival in patients with MYC and BCL6 DHL was unreached and was 21.6 months in patients with MYC and BCL2 DHL or THL. Conclusions: EBV infection in DHL/THL is rare (~1.5%). Cases of EBV + DHL/THL are largely similar to their EBV – counterparts clinicopathologically. Our findings expand the spectrum of EBV + B cell lymphomas currently recognised in the World Health Organisation classification and suggest differences between EBV + MYC and BCL2 DHL versus EBV+ MYC and BCL6 DHL that may have therapeutic implications. Abstract :